PENAMPILAN IKAN PANCHAX KUNING (Aplocheilus lineatus) PADA PEMBERIAN PAKAN YANG BERBEDA [The appearance of Aplocheilus lineatus on effect of different feed] - Novi Mayasari; Djamhuriyah S. Said (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2008)
The research on effect of feeds type on fish have common done. However information about appropriate feeds type for the growth and performance of Aplocheilus lineatus has been unknown well. The aim of this study is to determine the effect of different feed to growth, survival rate (SR) and body colour of A. lineatus. Three different feeds was used in this study, were commercial diet (pellet), Tubificidae, and Chironomus. Each treatment repeated three times. Ten A. lineatus juveniles 1.2 - 2.1 cm in length were kept in 60 x 30 x 30 cm5 aquarium for 3 months with observation period every two weeks. The result shows that there was not significant survival rate of/1, lineatus (p > 0.05). There is significant different in daily growth (length and weight) and body colour. Fish which fed with Tubificidae show the best growth of length (O.OS36 cm/day) and the best growth of weight (0.0327 g/day). Difference of appearance of fish body which clearly seen in male fish. Colour of fish body relatively shines and more brightly in fish which fed with Chironomus.